Поширення, екологічні та созологічні особливості Pleurotus calyptratus (Lindblad) Sacc. (Agaricales) в Україні - Прилуцький, О.В. (Український ботанічний журнал, 2011)
Представлены материалы о новых находках редкого в Европе вида Pleurotus саlуptrаtus (Lindblad) Sacc. из восточной части Украины. Рассматриваются его фенологические и субстратные предпочтения. Обобщены данные о редкости вида в пределах его ареала. Information about new records of Pleurotus calyptratus (Lindblad) Sacc., a rare species in Europe, from the eastern Ukraine is presented. Phenological features and substrate preferences of the species are discussed. Data about its rare occurence over the distribution range are summarized.